Medical and cardio-vascular emergency department visits during the COVID-19 pandemic in 2020: is there a collateral damage?: a retrospective routine data analysis - Slagman, Anna; Pigorsch, Mareen; Greiner, Felix; Behringer, Wilhelm; Bernhard, Michael; Bienzeisler, Jonas; Blaschke, Sabine; Burst, Volker; Dechant, Katharina; Dommasch, Michael; Ewen, Sebastian; Gries, André; et al. (Clinical research in cardiology, 2022)
Background: In this retrospective routine data analysis, we investigate the number of emergency department (ED) consultations during the COVID-19 pandemic of 2020 in Germany compared to the previous year with a special focus on numbers of myocardial infarction and acute heart failure. Methods: Aggregated case numbers for the two consecutive years 2019 and 2020 were obtained from 24 university hospitals and 9 non-university hospitals in Germany and assessed by age, gender, triage scores, disposition, care level and by ICD-10 codes including the tracer diagnoses myocardial infarction (I21) and heart failure (I50). Results: A total of 2,216,627 ED consultations were analyzed, of which 1,178,470 occurred in 2019 and 1,038,157 in 2020. The median deviation in case numbers between 2019 and 2020 was − 14% [CI (− 11)–(− 16)]. After a marked drop in all cases in the first COVID-19 wave in spring 2020, case numbers normalized during the summer. Thereafter starting in calendar week 39 case numbers constantly declined until the end of the year 2020. The decline in case numbers predominantly concerned younger [− 16%; CI (− 13)–(− 19)], less urgent [− 18%; CI (− 12)–(− 22)] and non-admitted cases [− 17%; CI (− 13)–(− 20)] in particular during the second wave. During the entire observation period admissions for chest pain [− 13%; CI (− 21)–2], myocardial infarction [− 2%; CI (− 9)–11] and heart failure [− 2%; CI (− 10)–6] were less affected and remained comparable to the previous year. Conclusions: ED visits were noticeably reduced during both SARS-CoV-2 pandemic waves in Germany but cardiovascular diagnoses were less affected and no refractory increase was noted. However, long-term effects cannot be ruled out and need to be analysed in future studies.
Gesehen am 04.09.2023